Exploiting the CIPRS model to analyse request performance used by second language speakers in an intercultural setting - Idrus, Faizah (cscanada.net www.cscanada.org, 2016)
It is important to understand request performance in interaction, especially when one is in a multicultural setting. This study has been dedicated to unravel the use of Cooperative Intercultural Pragmatics of Request Strategies Model (CIPRS) by second language learners in a global setting. It is found evident in this study that the second language learners do abide to a certain mental programme that has been instilled upon them and has played a very important role in their requesting performance.